Excited state kinetics in crystalline solids: Self-quenching in nanocrystals of 4,4′-disubstituted benzophenone triplets occurs by a reductive quenching mechanism - Kuzmanich, Gregory (2011)
We report an efficient triplet state self-quenching mechanism in crystals of eight benzophenones, which included the parent structure (1), six 4,4′-disubstituted compounds with NH 2 (2), NMe 2 (3), OH (4), OMe (5), COOH (6), and COOMe (7), and benzophenone-3,3′,4, 4′-tetracarboxylic dianhydride (8). Self-quenching effects were determined by measuring their triplet-triplet lifetimes and spectra using femtosecond and nanosecond transient absorption measurements with nanocrystalline suspensions. When possible, triplet lifetimes were confirmed by measuring the phosphorescence lifetimes and with the help of diffusion-limited quenching with iodide ions. We were surprised to discover that the triplet lifetimes of substituted benzophenones in crystals vary over 9 orders of magnitude from ca. 62 ps to 1 ms. In contrast to nanocrystalline suspensions, the lifetimes in solution only vary over 3 orders of magnitude (1-1000 μs). Analysis of the rate constants of quenching show that the more electron-rich benzophenones are the most efficiently deactivated such that there is an excellent correlation, ρ = -2.85, between the triplet quenching rate constants and the Hammet θ + values for the 4,4′ substituents. Several crystal structures indicate the existence of near-neighbor arrangements that deviate from the proposed ideal for "n-type" quenching, suggesting that charge transfer quenching is mediated by a relatively loose arrangement. © 2011 American Chemical Society.